Implementation of the best Interests of the Child Principles in Intercountry Adoption in Indonesia - Leonora Bakarbessy; Dian Purnama Anugerah (Yuridika, 2018)
Adoption of Indonesian children by foreigner is a form of intercountry adoption. In Indonesia such adoption is not prohibited but conditions are more difficult because it is a last effort or ultimum remedium for the best interests of the child. Therefore petition for intercountry adoption throught the court, its decision in the form of a court decision, because the proof as the same as the evidence in civil suit.This is defferent from the petition of national adoption.This paper discusses the implementation of the best interest of child’s principle in Indonesia and how to conduct intercountry adoption in Indonesia in order to avoid any attempts of illegal adoption. This paper concludes that the Indonesian Government has issued a number of laws and regulations govern the intercountry adoption. These laws require implying the principle of the best interest of children in order to protect the interest of children who is adopted by foreigner. In order to undertake the adoption, the court should decide that it is eligible after the Ministry of Social of the Republic of Indonesia approves adoption application.